Prognostic stratification of patients with AJCC 2018 pN1 disease in stage III oral squamous cell carcinoma - Ming-Hsien Tsai; Hui-Ching Chuang; Yu-Tsai Lin; Tai-Lin Huang; Fu-Min Fang; Hui Lu; Chih-Yen Chien (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Oral cancer with pT1-3N1 without extracapsular extension of the lymph node is classified as stage III according to the eighth edition of the AJCC staging system. Outcomes of a subgroup of patients classified as having stage III oral cancer with single nodal metastasis are observed to be various clinically. Therefore, such clinical outcomes for subgroup analyses in this cohort are necessary. Methods Patients with pT1-3N1 (based on the eighth edition of the AJCC staging system) oral cancer who underwent surgery between 2007 and 2016 were enrolled retrospectively for survival analyses. Results A total of 105 patients—including 28 patients with pT1N1 disease and 77 patients with pT2-3N1 disease—participated in the study. Pathological T classification was the only statistically significant prognosticator according to univariate analysis. The patients with pT1N1 disease showed better 5-year overall survival (OS), disease specific survival (DSS), and disease free survival (DFS) than those with pT2-3N1 disease (pT1N1 vs pT2-3N1, OS: 96.4% vs 72.2%, p = 0.004; DSS: 96.4% vs 77.3%, p = 0.021; DFS: 84.6% vs 62.3%, p = 0.023). Besides, there was no potential clinicopathological confounder which is significant associated with different pathological T classifications in this unique cohort. Conclusions Patients in the pT1N1 subgroup have significantly favorable prognosis than those with pT2-3N1 disease. Down-staging and reclassifying pT1N1 subgroup patients with oral cancer may be considered in tumor staging. Graphical Abstract